Baicalin protects H9c2 cardiomyocytes against hypoxia/reoxygenation‐induced apoptosis and oxidative stress through activation of mitochondrial aldehyde dehydrogenase 2. (20th December 2017) - Jiang, Wen‐Bin; Zhao, Wei; Chen, Hao; Wu, You‐Yang; Wang, Yi; Fu, Guo‐Sheng; Yang, Xiang‐Jun
Summary: Baicalin, a flavonoid glycoside separated from Scutellaria baicalensis, has cardioprotection against ischaemia/reperfusion (I/R) injury. Mitochondrial aldehyde dehydrogenase 2 (ALDH2) is considered as an endogenous protective mechanism against I/R injury depending on its anti‐oxidant and anti‐apoptotic characteristics. The present study demonstrates whether ALDH2 contributes to the cardioprotection of baicalin against hypoxia/reoxygenation (H/R)‐inudced H9c2 cardiomyocytes injury. Our results observed that H/R treatment resulted in a significant decrease in cells viability and obvious increases in caspase‐3 activity and apoptosis rate in H9c2 cells, while these alterations were evidently reversed by baicalin pretreatment. Simultaneously, baicalin mitigated H/R‐induced the decreases in the levels of ALDH2 mRNA and protein as well as the activity of ALDH2 in H9c2 cells. However, we found that daidzin, an ALDH2 antagonist, remarkably attenuated baicalin‐elicited inhibitory action on H/R‐induced the downregulation of cells viability and Bcl‐2 protein expression, and the upregulations of caspase‐3 activity, apoptosis rate, cytochrome c and Bax proteins expressions in H9c2 cells. In addition, baicalin reversed H/R‐induced oxidative stress as evidenced by the downregulation of malondialdehyde (MAD) and 4‐hydroxy aldehydes (4‐HNE) levels, the inhibition of endogenous reactive oxygen species (ROS) generation, and the downregulation of superoxide dismutase (SOD) activity induced by H/R treatment, while these effects were also blocked by daidzin. Furthermore, we found that Alda‐1, an ALDH2 agonist, also abolished H/R‐induced cytotoxicity, apoptosis, and oxidative stress, indicating that ALDH2 mediated H/R‐induced H9c2 cell injury. Overall, these results suggested that baicalin prevents H/R‐induced apoptosis and oxidative stress through enhancing ALDH activity and expression in H9c2 cardiomyocytes.